Corrective Effect of Sialic Acid on the Clotting of Factor VIII Deficient Blood - Rubin, H; Fernbach, T; Ritz, N. D (Thrombosis and Haemostasis, 1970)
Optimal concentrations of N-acetyl neuramic acid (NANA) accelerated the clotting of factor VIII deficient whole blood and plasma. There was no effect on normal plasma and certain other factor deficient plasmas.NANA increased thromboplastin formation by factor VIII deficient plasma, as measured by the Thromboplastin Generation Test.NANA possesses an inhibitory effect on rabbit brain thromboplastin and cephalin in recalcification tests, over the values of its controls, but-in sharp contrast, enhanced the effect of Russell Viper Venom (RVV) and RVV-cephalin.The amino sugar N-acetyl mannosamine, possessing common functional groups with NANA, also shortened the clotting time of factor VIII deficient whole blood and plasma.It is suggested that NANA acts as a cofactor to factor VIII which is present in trace amounts in hemophilic plasma.